Strategi Marketing Penerimaan Mahasiswa Baru Pada UPT Promosi dan PMB UMRI - Indari, Firul (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
An effective marketing strategy is the key to increasing student enrollment in higher education institutions. This study aims to analyze the marketing strategies implemented by the Promotion and New Student Acceptance Unit (PMB) of Muhammadiyah University of Riau (UMRI). Using a case study approach, this research examines the implementation of marketing strategies applied in the promotion and acceptance of new students. The results indicate that the use of social media as a promotional platform, the development of educational content, and collaboration with high schools are critical factors in increasing the number of applicants. Additionally, the presence of digital marketing strategies has had a significant impact on reaching a wider prospective student audience. This study suggests the need for continuous evaluation of marketing strategies to adapt to trends and the needs of prospective students to optimize efforts in attracting applicants.